Pseudomonas aeruginosa Virulence Factors Support Voriconazole Effects on Aspergillus fumigatus - Gabriele Sass; Pallabi Shrestha; David A. Stevens (Pathogens, 2021)
Pseudomonas aeruginosa and Aspergillus fumigatus are pathogens that are associated with deterioration of lung function, e.g., in persons with cystic fibrosis (CF). There is evidence that co-infections with these pathogens cause airway inflammation and aggravate pathology in CF lungs. Intermicrobial competition of P. aeruginosa and A. fumigatus has been described, but it is unknown how anti-fungal therapy is affected. The anti-fungal azole voriconazole (VCZ), supernatants of P. aeruginosa laboratory isolates PA14 or PAO1, or clinical isolate Pa10 independently inhibited biofilm metabolism of A. fumigatus isolates 10AF and AF13073. When VCZ and supernatants were combined at their IC50s, synergistic effects on A. fumigatus were found. Synergistic effects were no longer observed when P. aeruginosa supernatants were prepared in the presence of iron, or when P. aeruginosa mutants were lacking the ability to produce pyoverdine and pyochelin. Combination of pure P. aeruginosa products pyoverdine, pyochelin, and pyocyanin with VCZ showed synergistic anti-fungal effects. Combining VCZ with P. aeruginosa supernatants also improved its MIC and MFC against planktonic A. fumigatus. In summary, in the case of P. aeruginosa–A. fumigatus co-infections, it appeared that the P. aeruginosa co-infection facilitated therapy of the Aspergillus; lower concentrations of VCZ might be sufficient to control fungal growth.